MODEL PEMBELAJARAN AKUATIK BERBASIS PERMAINAN TRADISIONAL UNTUK MENINGKATKAN KETERAMPILAN BERENANG SISWA SEKOLAH DASAR - Bahtiyar Heru Susanto dan Ferawati Listianingsih (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2019)
Â AbstractThe purpose of this study was to produce a traditional game-based aquatic learning model to improve swimming skills in elementary school students. The long-term goal of this research is to embed the character of the love of the homeland in Indonesian youth so that a generation of people with character appears and is able to preserve Indonesian culture. Specific targets that will be achieved are introducing aquatic activities and increasing basic movement skills in elementary school children, while also instilling a sense of love for the homeland in the form of Indonesian culture. This research uses research & development methods (research & development) with a play approach. This method is believed to be effective in implementing aquatic learning because through traditional games developed, students do not realize that they have carried out the process of learning swimming skills by feeling happy, truly and pleasantly. The value of the character of love for the homeland that is expected by researchers can also be integrated in the aquatic learning process. This research consists of six steps, namely: (1) analyzing the product being developed; (2) developing initial products; (3) validation; (4) field trials; (5) product revisions; (6) final products. The results of the research are traditional game based aquatic learning model products. The product effectiveness test results showed that there was an increase in swimming skills based on the results of the pretest and posttest.Keywords: Aquatic learning, traditional games, swimming skills